Low‐dose naltrexone in Hailey–Hailey disease: the importance of dosing. (14th April 2020) - Acharya, P.; Mathur, M.
Abstract : Linked Article:  Jasans‐Barceló et al. Br J Dermatol 2020; 182 :1500–1503 .